Evaluación técnica y financiera del uso de un biorreactor anaerobio para el tratamiento de los residuos sólidos orgánicos generados en campo Rubiales como modelo de estandarización (2019)
The bioreactor is a tool that allows the treatment of solid organic waste in order to get to obtain renewable energy. Through this work The technical and financial evaluation related to the implementation of a bioreactor as a model in the Rubiales Fields and thus be able to determine the feasibility of replication in other fields. It was necessary to carry out a characterization of the solid waste generated by the field and with the determination of the organic compounds suitable for the process of anaerobic bioreaction. Likewise through a technical analysis it determined the variables that allow describing the generalities that should be have a bioreactor and its biomass.